A contribution towards the identification of the giant hogweed species (Heracleum, Apiaceae) naturalised in the British Isles with comments concerning their furanocoumarin content. (December 2013) - Denness, A.; Armitage, J. D.; Culham, A.
<x content-type="archive" xml:space="preserve">Abstract</x> The identity of giant hogweed species in the British Isles has been under debate in recent years. A morphometric analysis of fruit characters was used to study the number and identity of giant hogweed species occurring in these islands. Five clusters were identified, probably equating to species, to two of which the names Heracleum mantegazzianum Sommier & Levier and H. lehmannianum Bunge are tentatively attributed based on inclusion of type material. Details of the vittae and stylopodium are shown to provide a high level of discrimination and a preliminary key based on fruit characters is provided for the clusters identified. The legislative implications of these findings are considered and an amendment to Schedule 9 of the UK Wildlife and Countryside Act (1981) is advocated. An additional study of furanocoumarin content confirms that all naturalised populations of giant hogweed, regardless of identity, have the potential to cause phyto-photodermatitis and pose a threat to public health.